Penguatan Karakter Mahasiswa Melalui Filsafat Pancasila dalam Meningkatkan Tanggung Jawab Sosial di Perguruan Tinggi - Endang Isnawati; Rachel Meilisa Pakpahan; Ari Yohanes Setiawan Manik; Friska Rehulina Br Ginting; Sarah Theresia Zega; Ramsul Nababan (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
This research aims to examine how the philosophy of Pancasila can be used as a means of strengthening student character in increasing social responsibility in higher education. The research method used is a literature study, analyzing various relevant literature sources. The results show that the philosophy of Pancasila has values that can be used as a foundation in strengthening student character, such as the values of divinity, humanity, unity, democracy, and social justice. These values can help students develop social responsibility attitudes, such as empathy, tolerance, and awareness of the importance of contributing to society. This research also shows that integrating the philosophy of Pancasila in higher education can be one way to increase students' awareness and social responsibility. Thus, this research can contribute to the development of character education in higher education and increase awareness of the importance of social responsibility for students.